Coronary artery aneurysms: Variable presentations and management. (2018) - Rodriguez-Lozano, Jorge; Deanda, Abelardo; Gilani, Syed; Frank, Luba; Hornak, Patrik; Gogia, Bhanu; Marcondes, Felippe; Chavez, Miguel; Berbarie, Rafic F
No abstract available